Pengembangan wilayah Propinsi DIY (Pendekatan Teoritis) - Rudy Badrudin (Universitas Islam Indonesia, 1999)
The economic development process of Indonesia, in fact, has caused many distortions so that endanger the integration of nation. These distortions happened because of too centered development strategy causing distortion between central and region, and between region and region as well.